Effects of Rescheduling Hydrocodone on Opioid Prescribing in Ohio - Liu, Yingna (Pain Med, 2019)
BACKGROUND: We quantified opioid prescribing after the 2014 rescheduling of hydrocodone from schedule III to II in the United States using a state-wide prescription database and studied trends three years before and after the policy change, focusing on certain specialties. METHODS: We used Ohio’s state prescription drug monitoring program database, which includes all filled schedule II and III prescriptions regardless of payer or pharmacy, to conduct an interrupted time series analysis of the nine most prescribed opioids: hydrocodone, oxycodone, tramadol, codeine, and others. We analyzed hydrocodone prescribing trends for the physician specialties of internal medicine, anesthesiology, and emergency medicine. We evaluated trends 37 months before and after the rescheduling change. RESULTS: Rescheduling was associated with a hydrocodone level change of –26,358 (95% confidence interval [CI] = –36,700 to –16,016) prescriptions (–5.8%) and an additional decrease in prescriptions of –1,568 (95% CI = –2,296 to –839) per month (–0.8%). Codeine prescribing temporarily increased, at a level change of 6,304 (95% CI = 3,003 to 9,606) prescriptions (18.5%), indicating a substitution effect. Hydrocodone prescriptions by specialty were associated with a level change of –805 (95% CI = –1,280 to –330) prescriptions (–8.5%) for anesthesiologists and a level change of –14,619 (95% CI = –23,710 to –5,528) prescriptions (–10.2%) for internists. There was no effect on prescriptions by emergency physicians. CONCLUSIONS: The 2014 federal rescheduling of hydrocodone was associated with declines in hydrocodone prescriptions in Ohio beyond what had already been occurring, and hydrocodone may have been briefly substituted with codeine. These results indicate that rescheduling did have a lasting effect but affected prescribing specialties variably.